Soil solarization for mass scale production of arbuscular mycorrhizal fungal inoculum in Indian arid zone - RAO, V A; TARAFDAR, J C (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1995 to study the feasibility of large scale multiplication of arbuscular mycorrhizal fungal inoculum using soil solarization. At 0-10 cm maximum soil temperature in solarized plots varied from 6-9 0C higher compared to the non-solarized plots. A maximmum temperatUre of 68Â°C was observed at 0-10 cm depth in dry solarized plot. A significant reduction in the activities of various soil enzymes and micro-organisms was recorded in solarized plots coupled with irrigation and application of mustard cake. The effect was less at lower depths. The efficacy of summer irrigation and soil solarization combined with mustard cake was found toÂ· eradicate about 91 % native arbuscular mycorrhizal fungal spores at 0-10 cm. The build up of arbuscular mycorrhizal fungal spores was much better in solarized plots with maximum purity of 89% in solarized plots coupled with irrigation and amendment with mustard cake. The results indicated the possibility of adopting soil solarization for large scale multiplication of arbuscular mycorrhizal fungi by the farmers/nursery managers.